Penerapan Model Evaluasi CIPP pada Pelaksanaan Kegiatan KKN-T Unesa Surabaya 12 di RW 04 Lakarsantri - Nur Fitria; Adinda Salshabilla Yudha (Jurnal Pengabdian Pada Masyarakat, 2022)
APPLICATION OF THE CIPP EVALUATION MODEL IN THE IMPLEMENTATION OF UNESA SURABAYA 12 KKN-T ACTIVITIES IN RW 04LAKARSANTRI. The Covid-19 pandemic has an impact on all sectors of life, including online learning. KKN-T Surabaya 12 found various problems that occurred in RW 04 due to the Covid-19 pandemic, such as: learning loss, health aspects, to community services. For this reason, the Surabaya 12 KKN-T team carried out six programs which were divided into main and additional programs. The main programs include: Belajar bersama PAUD (BERTAUD), Mengaji Bareng (MABAR), and Balai Belajar. As for the additional programs, namely the Socialization Series, Senam Sehat Bersama, and Gebyar Gembira with the aim of forming a productive, intellectual, and literate RW O4 community. The implementation of KKN-T activities lasts for three months by realizing the program that has been proclaimed. After implementing the program, the Surabaya 12 KKN-T group evaluated the program using the CIPP model to determine the success of the program through four stages, namely context evaluation, input evaluation, process evaluation and product evaluation. The distribution of questionnaires, interviews and observations became the methods of collecting data and the results showed that the people of RW O4 were very happy and satisfied with the various activities that the Surabaya KKNT 12 had carried out.